2010
DOI: 10.1016/j.bpj.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

KCNE1 Remodels the Voltage Sensor of Kv7.1 to Modulate Channel Function

Abstract: The KCNE1 auxiliary subunit coassembles with the Kv7.1 channel and modulates its properties to generate the cardiac I(Ks) current. Recent biophysical evidence suggests that KCNE1 interacts with the voltage-sensing domain (VSD) of Kv7.1. To investigate the mechanism of how KCNE1 affects the VSD to alter the voltage dependence of channel activation, we perturbed the VSD of Kv7.1 by mutagenesis and chemical modification in the absence and presence of KCNE1. Mutagenesis of S4 in Kv7.1 indicates that basic residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
67
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 60 publications
6
67
1
Order By: Relevance
“…One possible explanation is that the distance between the S4 and S5 segments may be rather flexible in the absence of KCNE1 and Phe232 can avoid a collision with Phe279 during the course of activation. Wu et al 33 also reported that V221W and A223W (extracellular side of the S4 segment) mutations destabilize the open state of KCNQ1 channel only in the presence of KCNE1. This indicates that the upper part of S4 segment may be packed in the presence of KCNE1 because perturbation by bulky tryptophan is considered to be only effective in a packed environment for protein.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…One possible explanation is that the distance between the S4 and S5 segments may be rather flexible in the absence of KCNE1 and Phe232 can avoid a collision with Phe279 during the course of activation. Wu et al 33 also reported that V221W and A223W (extracellular side of the S4 segment) mutations destabilize the open state of KCNQ1 channel only in the presence of KCNE1. This indicates that the upper part of S4 segment may be packed in the presence of KCNE1 because perturbation by bulky tryptophan is considered to be only effective in a packed environment for protein.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, while the R1 and R2 mutants are effective both in the absence and presence of KCNE1, the R4 and R6 mutants are less effective in the presence of KCNE1 (ref. 33). As Phe232 and Phe279 destabilize the upstate in the presence of KCNE1, the destabilization effect on the upstate by R4/R6 mutation might be masked.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations